WAVEFORM IDENTIFICATION OF ALTIMETRY SATELLITE DATA OF SHALLOW AND DEEP WATERS IN SOUTHERN JAVA WATERS - Bisman Nababan; Romdonul Hakim; Danu Adrian; Jonson L Gaol (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACT Waveform patterns of satellite altimetry affect the accuracy of sea surface height estimation from the satellite. The waveform patterns found in the coastal waters are generally not in the ideal form (Brown-waveform), resulting inaccurate in sea surface height estimation. The objec-tives of this research were to identify patterns of the waveform and determine their variability. Satellite altimetry Jason-2 SGDR (Sensor Geophysical Data Record) type D data located in the southern Java island waters of the year of 2013 were used and downloaded from “NOAA's Comprehensive Large Array-data Stewardship System” (www.class.ncdc.noaa.gov) . Waveform identification and analyses were conducted along the satellite pass within the distance of 0-10 km, 10-50 km, and 50-100 km form the coastline. Results showed that the highest number of non-Brown-waveform was found within 0-10 km of the coastline (69%). Meanwhile, within the distance of 10-50 km and 50-100 km from the coastline, the number of non-Brown waveform was 5% and 3%, respectively. Brown waveform patterns could be found generally starting at 7.58 km from the coastline. Factors such as land near coastal waters, the depth and shape of the surface waters, aerosols in the atmosphere, building (example: lighthouse or ship) found in coastal areas suspected to be the cause of the noise in waveforms. Keywords: Borwn and non-Brown waveform, sea level height, altimetry satellite, identification